Comparison of 18F-NaF PET/CT and 18F-FDG PET/CT for Detection of Skull-Base Invasion and Osseous Metastases in Nasopharyngeal Carcinoma. (5th September 2018) - Zhang, Yin; Chen, Yue; Huang, Zhanwen; Zhang, Li; Wan, Qiang; Lei, Lei
Abstract : Our study aimed at comparing the diagnostic value of 18 F-NaF positron emission tomography-computed tomography (PET/CT) and 18 F-fluorodeoxyglucose (FDG) PET/CT for detection of skull-base invasion and osseous metastases in patients with nasopharyngeal carcinoma (NPC). Our study retrospectively analyzed 45 patients with pathologically proven NPC. They all underwent both 18 F-NaF PET/CT and 18 F-FDG PET/CT within a 7-day interval. Bone metastases were confirmed by follow-up using PET/CT, enhance-contrast computed tomography (CT), and magnetic resonance image (MRI). These two examinations were compared using per-patient-based analysis and per-lesion-based analysis. 18 F-NaF PET/CT detected 27 patients with skull-base invasion, whereas 18 F-FDG PET/CT detected 17 patients. 18 F-NaF PET/CT and 18 F-FDG PET/CT differed significantly in diagnosing skull-base invasion (p = 0.02 ) and sensitivity (p = 0.008 ). The sensitivity, specificity, and agreement rate of 18 F-NaF PET/CT for detecting bone metastatic lesions were 98.3%, 65.7%, and 92.9%, respectively; these values were 42.9%, 97.1%, and 51.9%, respectively, for 18 F-FDG PET/CT. 18 F-NaF PET/CT and 18 F-FDG PET/CT differed significantly in the number of osseous metastases detected (t = 2.45, p = 0.18 ) sensitivity (p < 0.0001 ) and specificity (p = 0.003 ). In patients with nasopharyngeal carcinoma, 18 F-NaF PET/CT assessed invasion of the skull base better and detected more osseous metastases than 18 F-FDG PET/CT.